ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN DI POLIKLINIK GIGI DAN MULUT PUSKESMAS SIDAMULYA BREBES PADA TAHUN 2012 - Panji Pratikno; Sutji Asri Tjitra Asmara; Recita Indraswary; Kusuma Arbianti (Jurnal Medali, 2013)
Patient satisfaction is one of the service indicator in evaluating the success of the health care services in primary health centers. The aim of the of the research is to analize patient satisfaction in dental clinic of sidamulya primary health centers Brebes based on four service dimensions, that are assurance, empathy, tangible, and reliability using Likert scale.This research is a descriptive analysis type with 100 people samples, the sampling is through Non Probability Sampling with sampling incidental method.The results showed that pastient satisfaction toward assurance dimension patients were satisfied with the average index value of 70,55. On the dimension of empathy showed quite satisfied index value that is 65,1. On the dimension of tangible showed satisfaction with the average index value of 70,16. On the dimension of reliability is quite satisfied with the average index value of 55,25. Overall,all service in dental clinic sidamulya primary health services are quite satisfied with the average index of value of 65,28.Levels of patient satisfaction in the dental clinic primary health centers Sidamulya Brebes from lowest to highest seen from the dimensions of reliability, empathy, physical appearance and assurance. Service in dental clinic brebes sidamulya primary health services are quite satisfied.Â Keywords: patient satisfaction, dimensions of satisfaction, primary health centers service